Pengembangan Media Film Dokumenter Yang Diangkat Dari Hasil Penelitian Pertumbuhan Anak Di Desa Jungkat - Bilqis, Khofifah Azmi; Candramila, Wolly; Mardiyyaningsih, Asriah Nurdini (Universitas Negeri Malang, 2024)
The learning media that lacks support can hinder communication between teachers and students. Engaging and innovative learning media can enliven the atmosphere during the learning process. Documentary film based on the malnutrition case in Jungkat Village is expected not only to enliven the atmosphere in the learning process but also provide information about important issues in society such as the Stunting case, which is currently a national topic. This study to develop and test the validity of a documentary film media addressing the topic of Stunting. The development of the documentary film media